Enteric glia as a player of gut-brain interactions during Parkinson’s disease - Thomasi, Beatriz; Valdetaro, Luisa; Ricciardi, Maria Carolina; Gonçalves de Carvalho, Marianna; Fialho Tavares, Isabela; Tavares-Gomes, Ana Lucia (Frontiers in Neuroscience, 2023)
The enteric glia has been shown as a potential component of neuroimmune interactions that signal in the gut-brain axis during Parkinson’s disease (PD). Enteric glia are a peripheral glial type found in the enteric nervous system (ENS) that, associated with enteric neurons, command various gastrointestinal (GI) functions. They are a unique cell type, with distinct phenotypes and distribution in the gut layers, which establish relevant neuroimmune modulation and regulate neuronal function. Comprehension of enteric glial roles during prodromal and symptomatic phases of PD should be a priority in neurogastroenterology research, as the reactive enteric glial profile, gastrointestinal dysfunction, and colonic inflammation have been verified during the prodromal phase of PD—a moment that may be interesting for interventions. In this review, we explore the mechanisms that should govern enteric glial signaling through the gut-brain axis to understand pathological events and verify the possible windows and pathways for therapeutic intervention. Enteric glia directly modulate several functional aspects of the intestine, such as motility, visceral sensory signaling, and immune polarization, key GI processes found deregulated in patients with PD. The search for glial biomarkers, the investigation of temporal–spatial events involving glial reactivity/signaling, and the proposal of enteric glia-based therapies are clearly demanded for innovative and intestine-related management of PD.